Financial Management Analysis of Micro, Small, and Medium Enterprise (MSME) in the Covid 19 Pandemic Era - Rohmatin, Laili; Muliawati, Unun Fiolita; Khoiriah, Lutfi Tasriful; Rahmawati, Lilik (JIFA (Journal of Islamic Finance and Accounting), 2021)
This study determined and analyzed the financial management of MSME. This case study was conducted in UD. Bintang Muda during the pandemic or commonly called the new normal. A qualitative method was carried out by collecting data through in-depth interviews gradually. The data obtained were collected, studied, and analyzed. As a reference, the information discovered in the data analysis was linked to previous theories or researches. The financial management at UD. Bintang Muda in facing changes and striving to survive in the new normal included shifting to a new financial management system from manual bookkeeping to electronic bookkeeping and reviewing expenses and income for further evaluation. The impacts caused by a pandemic demand MSME players to look for new innovations to survive and to be more responsive to changes in the business climate, especially during the new normal. UD Bintang Muda implemented a new strategy by increasing the quality of packaging to compete in the high-end market. Keywords: Financial Management; Pandemic; Covid 19; MSME